2020
DOI: 10.1186/s40816-020-00170-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant and anti-inflammatory potency of Lepidium pinnatifidum Ledeb

Abstract: Backgroound: Lepidium pinnatifidum is a multipurpose, beneficial plant and known well for its indigenous therapeutic standards. Current study is aimed to investigate antioxidant and anti-inflammatory potency of Lepidium pinnatifidum. L. pinnatifidum dried powder was extracted with crude methanol (LPM) and then fractionated with various solvents to get respective fractions, termed as, n-hexane (LPH), chloroform (LPC), ethyl acetate (LPE), butanol (LPB) and the aqueous fraction (LPA). Fractions were evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The antioxidant activity of phenolics and flavonoids primarily depends on the presence of hydroxyl groups [26]. In a previous study on A. bracteosa, the highest amount of phenolic content was found in crude extracts prepared in more polar solvents (10.75 ± 0.70 µg GAE/mg DW of methanolic extracts) than the non-polar solvent systems (0.33 ± 0.0 µg GAE/mg DW demonstrated by n-hexane extract).…”
Section: Discussionmentioning
confidence: 88%
“…The antioxidant activity of phenolics and flavonoids primarily depends on the presence of hydroxyl groups [26]. In a previous study on A. bracteosa, the highest amount of phenolic content was found in crude extracts prepared in more polar solvents (10.75 ± 0.70 µg GAE/mg DW of methanolic extracts) than the non-polar solvent systems (0.33 ± 0.0 µg GAE/mg DW demonstrated by n-hexane extract).…”
Section: Discussionmentioning
confidence: 88%
“…The antioxidant activity of phenolics and avonoids primarily depends on the presence of hydroxyl groups [33]. Current study demonstrated signi cantly higher values of TPC and TFC in transformed regenerants as compared to untransformed plants.…”
Section: Discussionmentioning
confidence: 48%